Acute Promyelocytic Leukemia: Simplifying Treatment in a Resource Poor Setting - Bhise, Rohan; Ahmed, Imtiaz; Imtiaz, Sapna (Asian Pacific Journal of Cancer Care, 2021)
Introduction: Acute promyelocytic leukemia (APL) is a distinct leukemia which can be treated with differentiating agents alone.Treatment without chemotherapy decreases the cost of treatment and the need for supportive care. Here we present analysis of APL patients treated with arsenic trioxide (ATO)-all trans retinoic acid (ATRA) without chemotherapy in our hospital. Patients and Methods: Forty three patients with newly diagnosed APL were treated with arsenic trioxide(ATO ) and All trans retinoic acid (ATRA) during induction treatment. For consolidation ATRA 45 mg /m2 for two weeks every four weeks was administered for twenty eight weeks. ATO was administered for four cycles, with a cycle length of eight weeks. The drug was administered at 0.15 mg/kg/d for five days per week for four weeks during each cycle.Patients were followed up with once in three month hemogram and once in six month reverse-transcriptase polymerase chain reaction (RT-PCR) for two years and yearly thereafter. Results: The morphologic complete remission (CR) rate was 86.04%.The most common cause of remission failure was early death due to bleeding. None of the low risk patients died during induction therapy. The most important prognostic factor for early mortality was a high white blood cell (WBC) count at presentation. The median overall survival (OS) has not been reached.The two year OS was 83.4% and the three year OS was 74.8%.The estimated five year survival was 74.8%. At a median follow up of 42.6 months the estimated five year survival in the low-intermediate risk group was 93.3% and 59.1% in the high risk group Conclusion: ATO –ATRA can be considered as a treatment option for frontline treatment of all risk APL patients in resource poor settings.The results can be better with better supportive care to prevent early mortality and by salvaging patients who relapse.